Form the quadratic equation if its roots are -3 and 4
jatin258:
x²-(-3+4)x+(-3*4) then x²-x-12. hence equation is fromed..
Answers
Answered by
3
Here's the answer to your question
Hope it helps
Hope it helps
Attachments:
![](https://hi-static.z-dn.net/files/dbf/99fb4d96fd200ff7415a728f5764544f.jpg)
Answered by
2
hey dear
here is your answer
we assume
a = -3
b = 4
firstly we do sum a+b = -3 +4 = -1
then we do product a * b. = -3 *4 = -12
then we use formula
x^2 - ( a+ b) x + ( ab)
we put the value according to this formula
x^2 + ( -1) x + (- 12)
hence quadratic equation is
x^2 - x - 12
hope it helps
thank you
here is your answer
we assume
a = -3
b = 4
firstly we do sum a+b = -3 +4 = -1
then we do product a * b. = -3 *4 = -12
then we use formula
x^2 - ( a+ b) x + ( ab)
we put the value according to this formula
x^2 + ( -1) x + (- 12)
hence quadratic equation is
x^2 - x - 12
hope it helps
thank you
Similar questions